Large, Synoptic and Meso Scale Variations of the Baiu Front, during July 1982: Part I:Cloud Features - Akiyama, Takako (Journal of the Meteorological Society of Japan, 1989)
The large, synoptic and meso scale features of the Baiu front that occurred during July 1982 are described, based mainly on GMS-IR digital data.The periods of synoptic and meso scales were determined by spectral analysis of the cloud amounts in the Baiu front.Attention was focused on three subjects:(1) the large-scale (5-day mean) features during the active phase of the Baiu front, (2) the difference of synoptic-scale (having a period of about six days) and mesoscale (a period of a few days to one day) variations in cloud features occurring over the continent (the western part of the Baiu front) from those occurring over the NW Pacific (the eastern part) and (3) the difference in frontal activity between 00GMT and 12GMT. During the active phase characterized by large cloud amounts in the 5-day mean, large-scale baro-clinicity, low-level southwest to west-southwest wind found south of the frontal zone, moisture flux convergence and the horizontal gradient of equivalent potential temperature (θe) in the lower layer of the frontal zone are strong, compared with those found during the inactive phase. The large-scale features around the frontal zone over the continent differ from those over the .NW Pacific.These regional differences in the large-scale features are reflected in the synoptic and meso scale cloud features in the frontal zone. Over the continent where the frontal zone is characterized by a strong low-level wind and an air mass of high θe, the synoptic-scale and mesoscale variations are prominent.The mesoscale cloud clusters that develop with a one-day period have diameters of -500km and consist of convective clouds. Over the continent, the one-day period variations of clouds are related to the underlying topography; mesoscale cloud clusters tend to develop in the basin areas around 00GMT and in the high altitude regions around 12GMT.There was hardly any meander of the frontal zone with a synoptic-scale period. Over the NW Pacific where the Baiu front is characterized by baroclinicity and an air mass of rather lower θe, the frontal zone meanders with a synoptic-scale period.The mesoscale cloud clusters that compose the synoptic-scale cloud systems are relatively large (-100Okm) and develop having periods of a few days.The mesoscale clusters consist of areas of narrow convective and wide stratiform clouds. In the frontal zone over Japan, both synoptic and meso scale variations show transitional features from those over the continent to those over the NW Pacific. Over the continent, the Baiu frontal cloud zone shifts north about 200km around 00GMT.The shift is associated with the increase in the low-level moisture flux south of the frontal zone, the increases in the low-level moisture flux convergence and middle-level moisture content in the frontal cloud zone. In Part II of this study, the structure of the Baiu front and features of sysnoptic and meso scale Baiu frontal disturbances will be clarified by analysis of relative vorticity fields. c 1989, Meteorological Society of Japan